2017
DOI: 10.7759/cureus.1903
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Burden of Rotavirus Gastroenteritis: A Prospective Study

Abstract: BackgroundIn Saudi Arabia, there is a lack of recently published, appropriately conducted epidemiological studies on rotavirus (RV) diarrhea, which emphasizes the need for up-to-date and comprehensive studies.ObjectiveOur objective was to provide more recent data on the clinical and epidemiological characteristics as well as the economic burden of RV diarrhea among young children admitted to a tertiary care hospital in the city of Riyadh in the year prior to the initiation of the RV vaccine.DesignWe conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 15 publications
3
3
1
Order By: Relevance
“…In our study, vomiting, as a symptom of the disease, was present in 84% of infants with RVGE. The results similar to ours were obtained in their study by Nahari et al, where vomiting was reported as a symptom in 81.3% (15). A slightly lower incidence of vomiting was observed in the study of Karampatsas et al, where it was 74% (13) and in the study by Arístegui et al, where it was 69.1% (14).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In our study, vomiting, as a symptom of the disease, was present in 84% of infants with RVGE. The results similar to ours were obtained in their study by Nahari et al, where vomiting was reported as a symptom in 81.3% (15). A slightly lower incidence of vomiting was observed in the study of Karampatsas et al, where it was 74% (13) and in the study by Arístegui et al, where it was 69.1% (14).…”
Section: Discussionsupporting
confidence: 90%
“…In our study, Rotavirus infection occurred throughout, with statistically significant occurrence in March. The results of compatibility with ours were obtained by Shrestha et al who conducted his research in the territory of Nepal (12), Aristegui et al in the territory of Spain (14), as well as Nahari et al in the territory of Saudi Arabia (15). Different results from ours were reported in Thailand, where the highest incidence was recorded in the summer months (16) as well as during the summer rains in Ethiopia (17).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations